2011
DOI: 10.5539/ies.v4n3p100
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Visual-Motor Integration Skills of 60-72 Month Children from High and Low Socio- Economic Status As Regard Age Factor

Abstract: The aim of this study is to define whether there are any differences in the visual-motor integration skills of 60-72-month-old children at low and high socio-economic status as regard the age factor. The study was conducted on a total of 148 children consisting of 78 children representing low socio-economic status and 70 children representing high socio-economic status in the city center of Edirne. In the study, the Beery-Buktenica Developmental Test of Visual Motor Integration (VMI-5th), which was developed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
2
9
0
4
Order By: Relevance
“…Two studies investigating preschool children aged three years six months to five years, respectively, concluded that age and geographic location affected VMI scores [ 44 , 48 ]. Similar findings were noted previously when 60 to 72-month-old children were studied [ 43 ]. Additionally, this study concluded that age and socioeconomic status, commonly associated with location, were found to impact VMI scores.…”
Section: Review Of the Literaturesupporting
confidence: 91%
“…Two studies investigating preschool children aged three years six months to five years, respectively, concluded that age and geographic location affected VMI scores [ 44 , 48 ]. Similar findings were noted previously when 60 to 72-month-old children were studied [ 43 ]. Additionally, this study concluded that age and socioeconomic status, commonly associated with location, were found to impact VMI scores.…”
Section: Review Of the Literaturesupporting
confidence: 91%
“…This study's results have also demonstrated the associations between various socioeconomic variables on preschoolers' VMI performance. Many researchers regarded socioeconomic status as one of the most influential factors that can have direct negative impacts on the development of young children [23,[42][43][44]. We found that a higher proportion of children enrolled in KEMAS (public) preschools had reduced VMI performance than those enrolled at private, feepaying preschools.…”
Section: Plos Onementioning
confidence: 73%
“…У истраживању које је за предмет имало испитивање визуелно-моторне координације код 22 дјеце са хемипарезом, резултати који одступају 2 SD пронађени су код 2 испитаника што говори о добро развијеној способности код ових испитаника (Димић и Солдо, 1990). Испитујући визуелно-моторну координацију аутори се слажу да је ова способност битна не само у усвајању школских знања већ и у свакодневним, практичним активностима као што су: везивање пертли, слагање пазли, вожња бицикла, кориштење компјутера (Ercan, Ahmetoğlu & Aral, 2011;Pereira et al, 2011). Резултати једног новијег истраживања наглашавају да је визуелно-моторна координација важан аспект психомоторног развоја дјеце што захтјева њено праћење и стварање повољнијих услова за њену стимулацију посебно у периоду до 10 године када се и најбрже развија.…”
Section: методологијаunclassified